Condensate Water Processing of Split-Unit Air Conditioning System on Commercial Building - Henry Nasution; Nurul Hanim Aubaidellah (Universitas Mercu Buana, 2024)
This research investigates the feasibility and potential for water recovery from condensate produced by a split-unit air conditioning (AC) system in a commercial building, focusing on Scholar’s Inn UTM (SIUTM) in Johor, Malaysia. The study involves the collection and measurement of condensate water from 243 AC units under various operational conditions. The results indicate that the building can produce up to 4,781 liters of condensate per day, amounting to an annual total of approximately 1,721,160 liters. This significant volume highlights the potential for utilizing condensate as an alternative water source, especially in regions with similar hot and humid climates. Water quality analysis was conducted to evaluate the suitability of the condensate for various applications. The condensate water exhibited a pH of 7.17, Total Dissolved Solids (TDS) of 1.0 mg/L, and a copper (Cu) concentration of 1.1 mg/L. While these parameters indicate that the water is within acceptable ranges for non-potable uses, such as irrigation or cooling tower makeup water, the copper concentration slightly exceeds the standard for potable water, necessitating treatment such as reverse osmosis before consumption. The study’s findings underscore the environmental and economic benefits of condensate recovery, offering a sustainable solution to water scarcity issues in commercial buildings. By integrating condensate recovery systems, facilities can reduce their reliance on traditional water sources, contributing to broader water conservation efforts. Future research should explore the long-term viability and scalability of such systems in various building types and climates.